2021
DOI: 10.1242/dev.197673
|View full text |Cite
|
Sign up to set email alerts
|

The trophoblast clock controls transport across placenta in mice

Abstract: In mammals, 24-h rhythms of physiology and behavior are organized by a body-wide network of clock genes and proteins. Despite the well-known function of the adult circadian system, the roles of maternal, fetal and placental clocks during pregnancy are poorly defined. In the mature mouse placenta, the labyrinth zone (LZ) is of fetal origin and key for selective nutrient and waste exchange. Recently, clock gene expression has been detected in LZ and other fetal tissues; however, there is no evidence of a placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…placental trophoblast cell line (BeWo) cell line, ABCB1 mRNA expression and ABCB1 protein levels were found to have rhythms peaking at 30 and 36 hours after circadian clock synchronization. 81 Overall, the removal of xenobiotics through P-gp is a phenomenon that occurs in various organs, and the confluence of data generally shows higher efflux activity during the active phase consistent with what has been observed in the brain. The precise peaks and troughs vary among organs and animal species; however, the underlying timekeeping mechanism is likely the same.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...supporting
confidence: 73%
See 1 more Smart Citation
“…placental trophoblast cell line (BeWo) cell line, ABCB1 mRNA expression and ABCB1 protein levels were found to have rhythms peaking at 30 and 36 hours after circadian clock synchronization. 81 Overall, the removal of xenobiotics through P-gp is a phenomenon that occurs in various organs, and the confluence of data generally shows higher efflux activity during the active phase consistent with what has been observed in the brain. The precise peaks and troughs vary among organs and animal species; however, the underlying timekeeping mechanism is likely the same.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...supporting
confidence: 73%
“…In addition, in the human placental trophoblast cell line (BeWo) cell line, ABCB1 mRNA expression and ABCB1 protein levels were found to have rhythms peaking at 30 and 36 hours after circadian clock synchronization. 81 Overall, the removal of xenobiotics through P-gp is a phenomenon that occurs in various organs, and the…”
Section: Livermentioning
confidence: 99%
“…Key mediators in this transfer of information to the fetus include maternal melatonin and maternal glucocorticoids. Nevertheless, further research is crucial to fully understand the intricate circadian relationship between the mother, placenta, and fetus 73–75 …”
Section: Maternal‐fetal Circadian System Organization: Unraveling The...mentioning
confidence: 99%
“…For the fetus that cannot receive light stimulation in the uterus, transplacental glucose transport from maternal blood after food intake can be a direct signal to detect the maternal circadian rhythm during pregnancy [29]. A recent study reported that the trophoblast controls transport across the placenta in mice during pregnancy by regulating the circadian expression and activity of the xenobiotic efflux pump, ATP-binding cassette sub-family B member 1 (ABCB1) [30]. Accordingly, we speculate that the uterus is prepared to synchronize its function with food intake to provide an adequate environment for the fetus.…”
Section: Feeding Directly Regulates the Uterine Clock Rhythm In Micementioning
confidence: 99%